Just Words : Constitutional Rights and Social Wrongs. - Bakan, Joel (University of Toronto Press, 1997)
Joel Bakan argues that the Canadian Charter of Rights (1982) has failed to promote social justice because it is administered by a conservative judiciary and because social and economic conditions constantly interfere with its principles.